2008
DOI: 10.1128/jvi.01708-07
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1B55K Region Is Required To Enhance Cyclin E Expression for Efficient Viral DNA Replication

Abstract: Adenoviruses (Ads) with E1B55K mutations can selectively replicate in and destroy cancer cells. However, the mechanism of Ad-selective replication in tumor cells is not well characterized. We have shown previously that expression of several cell cycle-regulating genes is markedly affected by the Ad E1b gene in WI-38 human lung fibroblast cells (X. Rao, et al., Virology 350:418-428, 2006). In the current study, we show that the Ad E1B55K region is required to enhance cyclin E expression and that the failure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(112 citation statements)
references
References 92 publications
9
103
0
Order By: Relevance
“…We previously have reported that Ad E1B55K protein is involved in the induction of cell cycle-related genes, including cyclin E. 24 E1B55K-deleted Ads fail to induce cyclin E expression in normal cells and therefore their replication is restricted. 25 However, E1b55K-deleted oncolytic Ads can still efficiently induce cyclin E in cancer cells with dysregulated cyclin E and carry out sufficient oncolytic replication. 25,26 In this study, we observed that expression of cyclin E was downregulated in response to the treatment with I3C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously have reported that Ad E1B55K protein is involved in the induction of cell cycle-related genes, including cyclin E. 24 E1B55K-deleted Ads fail to induce cyclin E expression in normal cells and therefore their replication is restricted. 25 However, E1b55K-deleted oncolytic Ads can still efficiently induce cyclin E in cancer cells with dysregulated cyclin E and carry out sufficient oncolytic replication. 25,26 In this study, we observed that expression of cyclin E was downregulated in response to the treatment with I3C.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, E1b55K-deleted oncolytic Ads can still efficiently induce cyclin E in cancer cells with dysregulated cyclin E and carry out sufficient oncolytic replication. 25,26 In this study, we observed that expression of cyclin E was downregulated in response to the treatment with I3C. As a consequence of repression of cyclin E induction, pretreatment with I3C repressed replication of Ads up to 10-fold (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these conditions, 213 µW/cm 2 UV type-C was produced, generating a total UV dose of 639 J/m 2 after 5 min exposure. Irradiated viruses were then used to infect Saos-2 cancer cells, in which Ads cannot replicate as well as in HEK293 and A549 cells [20]. Four hours (h) after infection, virus particles in the medium were removed by washing the cells with fresh media.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…7 Other efforts that introduce mutation into E1A and/or E1B genes can improve the specificity of viral propagation in tumor cells, but often lead to decreased efficiency of viral replication. [8][9][10] An alternative strategy for tumor-selective adenoviral replication is to delete the Ad E1A and/or E1B, which are dispensable in tumor cells. 11,12 E1A and E1B are the immediate-early viral genes, and the expression of E1A and E1B can act as the main transactivator of other viral promoters, force quiescent cells into Cancer gene therapy requires tumor-specific delivery and expression of a transgene to maximize antitumor efficacy and minimize side effects.…”
Section: Introductionmentioning
confidence: 99%